Bimbingan Islami Pada Muallaf Di Yayasan Al Istiqomah Denpasar Bali - Septiana Eka Pratiwi; Yohandi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
Indonesia is one of the countries that does not give space for its citizens to have no religion and do not believe in God. People are free to choose their religion, but they are not free not to be religious, so that religious identity is included in identity cards and other documents. The purpose of this study was to describe the implementation of Islamic guidance given to converts to Islam at the Al Istiqomah Foundation in Denpasar. This research method uses qualitative research methods with the type of case study research. The results of the research from Islamic guidance at the Al Istiqomah Foundation, namely the religious and spiritual conditions of converts are getting better. Over time, converts began to feel calm in embracing Islam while following the guidance of converts. This condition becomes better when compared to before following the guidance.